2021
DOI: 10.1002/cbdv.202100071
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Chemical Differentiation between Tunisian Populations of Pinus halepensis, Pinus brutia, and Pinus pinaster

Abstract: The lipid fraction of seeds from different pine species and populations was studied regarding total lipid content, fatty acid profile and vitamin E composition. The investigated seeds contained a high percentage of lipid (13.6 to 31.5 %). Lipid fractions were found to be rich in vitamin E, which varied significantly among species and populations. P. halepensis (Ph−Hn) showed the highest content of vitamin E (256.3 mg/kg of seeds) and the uppermost content of α‐tocopherol (44 mg/kg). However, P. halepensis (Ph−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Essential oils have several medicinal properties that could be useful in the pharmaceutical field. Environmental factors have a great impact on the essential oil yield, composition, and, consequently, its biological activity [ 4 , 13 ]. This can be recognized from different earlier reports [ 6 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils have several medicinal properties that could be useful in the pharmaceutical field. Environmental factors have a great impact on the essential oil yield, composition, and, consequently, its biological activity [ 4 , 13 ]. This can be recognized from different earlier reports [ 6 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously dealt with the constituents of P. halepensis and P. pinea needles, but the composition of the essential oil usually varies due to the geographic location, climatic conditions, and the time of collection; this may also affect its biological potential [ 4 , 9 , 12 , 13 ]. To the best of our knowledge, no comparative study has been published related to the chemical composition and anthelmintic and antimicrobial activities of P. halepensis and P. pinea essential oils in Libya, reflecting the impact of geographic difference and ecological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a study comparing the fatty acids of Pinus halepensis, Pinus brutia and Pinus pinaster seeds, it was found that the seeds of P. halepensis and P. brutia were significantly richer than those of P. pinaster in terms of α-tocopherol, γ-tocopherol, γ-tocotrienol, and δ-tocopherol. The same study revealed that while P. halepensis seeds had the highest α-tocopherol content, P. brutia seeds contained a higher amount of γ-tocopherol than other species (Khouja et al 2021). However, the composition of fatty acids may differ between individuals of the same species grown in different locations.…”
Section: Bioresourcescommentioning
confidence: 95%
“…P. halepensis is a species widely distributed in the Mediterranean basin and is used in traditional medicine to treat sexual problems, as an anti-inflammatory, and as an antidiabetic [ 5 ]. This oil is rich in monounsaturated and polyunsaturated fatty acids, the main components of linoleic, oleic, and palmitic acids (about 5%) [ 6 , 7 ]. This oil exhibits antioxidant activity and can delay the progression of chronic diseases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%